Β-D-glucan from marine yeast Debaryomyces hansenii BCS004 enhanced intestinal health and glucan-expressed receptor genes in Pacific red snapper Lutjanus peru. (June 2020) - Reyes-Becerril, Martha; Angulo, Miriam; Sanchez, Veronica; Guluarte, Crystal; Angulo, Carlos
Abstract: Previous studies have shown that marine yeast Debaryomyces hansenii BCS004 (also known as Dh004) has a potential biotechnological application. The aim of this study was to investigate the structural characterization, antioxidant properties and possible health inductor of dietary β-D-glucan BCS004. In this study, a glucan BCS004 was obtained containing (1–6)-branched (1–3)-β-D-glucan with low molecular weight and a high purity of 90 and 91.7% for one and 4 h, respectively. β-D-glucan BCS004 showed higher antioxidant activity, including DPPH radical and superoxide anion scavenging, β-carotene bleaching inhibition, and iron chelation activity. An in vitro study showed that β-D-glucan BCS004 was safe for peripheral blood leukocytes inducing proliferative effects. Moreover, in an in vivo study using β-D-glucan BCS004 no histopathological damages or intestinal inflammation were observed in fish. The gene expression analysis highlighted that dietary β-D-glucan BCS004 could also up-regulate glucan and macrophage receptor genes in intestine, such as C-type lectin (CTL) and macrophage mannose receptors (MMR). Overall, the results demonstrated that β-D-glucan from D. hansenii BCS004 could be an immunostimulant with antioxidant properties and beneficial effects on intestinal health in fish. Highlights: Glucan from marine yeast Debaryomyces hansenii BCS004 (Dh004) was characterized. NMR indicated structures of (1–6)-branched (1–3)-β-D-glucan with low molecular weight. β-D-glucan BCS004 exhibited significant free radical scavenging capacity. β-D-glucan BCS004 is not cytotoxic for peripheral blood leukocytes and intestine. β-D-glucan BCS004 up-regulated glucan and cellular receptor genes in intestine.